Two-component heat-conducting gel with high heat conductivity, low viscosity and high thixotropy

The dual-component thermal gel, composed of specific silicon oil components, addresses settling and phase separation issues by achieving high thermal conductivity and thixotropy, allowing stable room temperature storage and high-temperature operation up to 200°C.

CN119708861AActive Publication Date: 2025-03-28HEXENE ELECTRONIC TECH (JIANGSU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411964798.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing dual-component gels experience settling and phase separation at room temperature during storage and are limited in high-temperature usage, typically not exceeding 200°C.

Method used

A dual-component thermal gel comprising components A and B, where A includes methyl acrylate-based and linear isobutene-based silicon oils with specific additives, and B includes cyano and hydrogen silicon oils, processed to achieve a high thermal conductivity, low viscosity, and high thixotropy, allowing for stable storage and high-temperature operation.

Benefits of technology

The gel exhibits high thermal conductivity, low viscosity, and high thixotropy, preventing settling and phase separation at room temperature and enabling long-term use up to 200°C.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a two-component heat-conducting gel with high heat conductivity, low viscosity and high thixotropy, a modifier and a treating agent are respectively suitable for forming an intermolecular acting force network structure of polar molecules in a system of a heat-conducting component A and a gel component B, and the improvement of the thixotropy of the heat-conducting component A and the gel component B and the improvement of the room-temperature storage stability are facilitated. Linear isopropenyl-terminated silicone oil and cyano-terminated silicone oil are compounded and interact with the modifier and the treating agent respectively, so that the thixotropy and room temperature stability of the component A and the component B are further improved. The double-component heat-conducting gel disclosed by the invention has the properties of high heat conductivity, low viscosity and high thixotropy, can resist sedimentation and phase splitting during storage at room temperature, is resistant to high temperature and can be used at 200 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive gels, and in particular relates to a two-component thermal conductive gel with high thermal conductivity, low viscosity and high thixotropy. Background Art

[0002] Thermally conductive gel is a gel-like thermally conductive material made by kneading, stirring and encapsulating a composite thermally conductive filler made of silicone. It includes thermally conductive silicone grease made with various silicone resins as the base and added with metals with high thermal conductivity such as silver, copper, and aluminum, and thermally conductive gel materials made with various silicone oils as the base and added with thermally conductive fillers such as zinc oxide, magnesium oxide, aluminum nitride, and boron nitride. They are widely used in heat dissipation of electronic components.

[0003] Thermally conductive gel has the advantages of good affinity, weather resistance, high and low temperature resistance, and good insulation. At the same time, it has strong plasticity and can fill uneven interfaces, which can meet the heat transfer needs of various applications.

[0004] Existing two-component gels will undergo sedimentation and stratification when stored at room temperature, and the operating temperature cannot be too high, and often cannot be used at 200°C. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy to avoid sedimentation and phase separation when stored at room temperature in view of the shortcomings of the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows: A two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy, comprising a thermally conductive component A and a gel component B; Wherein, the thermal conductive component A includes the following components in parts by mass: 3-5 parts of methacrylate-terminated silicone oil; 2-5 parts of linear isopropenyl-terminated silicone oil; 1-3 parts of modifier; Cross-linking accelerator 0.01-0.05 parts; Li7La3Zr2O 12 35-55 parts of micro powder; 35-50 parts of La2Ce2O7 powder; Gel component B includes the following components in parts by mass: 5-8 parts of cyano-terminated silicone oil; 5-8 parts of hydrogen silicone oil; 5-8 parts of treatment agent; Complexing agent 0.001-0.005 parts; 40-50 parts of titanium monoxide powder; 35-40 parts of MgFe2O4 fine powder.

[0007] Specifically, the thermal conductive component A and the gel component B are mixed in a mass ratio of 1-1.2:1.

[0008] Specifically, in the thermal conductive component A, the methacrylate-terminated silicone oil has a dynamic viscosity of 200-300 cst and a branching factor of 0.2-0.3; and the linear isopropenyl-terminated silicone oil has a dynamic viscosity of 150-250 cst.

[0009] Specifically, in the thermal conductive component A, the modifier is a mixture of isooctyl octadecanoate and isononyl gluconate in a mass ratio of 1 to 1.2:1; the cross-linking accelerator is any one of manganese oleate, nickel isostearate, and cobalt isodecanoate, or a mixture of two of them in a mass ratio of 1 to 1.2:1.

[0010] Specifically, in the thermal conductive component A, the Li7La3Zr2O 12 The particle size of the micro powder is 30 to 70 microns; the particle size of the La2Ce2O7 micro powder is 5 to 10 microns.

[0011] Specifically, in the thermal conductive component B, the cyano-terminated silicone oil has a dynamic viscosity of 200-300 cst and a branching factor of 0.5-0.7; the hydrogen-containing silicone oil has a dynamic viscosity of 150-250 cst and a branching factor of 0.3-0.5.

[0012] Specifically, in the thermal conductive component B, the treatment agent is any one of phenyltriethoxysilane, hydrogenated castor oil, and palmitic acid, or a mixture of two of them in a mass ratio of 1 to 1.2:1; the complexing agent is any one of oleylamine, dimethyl maleate, and tin benzoate, or a mixture of two of them in a mass ratio of 1 to 1.2:1.

[0013] Specifically, in the thermal conductive component B, the particle size of the titanium monoxide powder is 20-50 microns; the particle size of the MgFe2O4 powder is 1-3 microns.

[0014] Furthermore, the present invention also provides a method for preparing the above-mentioned two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy, comprising the following steps: (1) Preparation of thermal conductive component A: Step A1: adding a portion of linear isopropenyl-terminated silicone oil to methacrylate-terminated silicone oil, heating to 40-60° C., stirring and mixing, controlling the stirring rate at 300-500 rpm for 10-30 minutes, stirring and cooling to room temperature to obtain a first mixed solution of component A; Step A2: Stir the first mixed solution of component A obtained in step (A1) in an ice-water bath at a stirring rate of 300-500 rpm, slowly dropwise add the modifier, and the dropping time is controlled within 1-3 hours. After the dropping is completed, stir for another 20-40 minutes to obtain a second mixed solution of component A; Step A3: Keep stirring in an ice-water bath at a stirring rate of 300-500 rpm, add the remaining amount of linear isopropenyl-terminated silicone oil to the second mixed solution of component A obtained in step (A3), and stir for 1-3 hours to obtain a third mixed solution of component A; Step A4: Keep stirring in an ice-water bath at a stirring rate of 200-400 rpm, slowly dropwise add a crosslinking accelerator to the third mixed solution of component A obtained in step (A3), and control the dropping time to be 6-12 minutes. After the dropping is completed, continue stirring for 3-5 minutes, and stir and heat to room temperature under sealing conditions to obtain a fourth mixed solution of component A; Step A5: Li7La3Zr2O 12 Add the powder and La2Ce2O7 powder together into the fourth mixed solution of component A obtained in step (A4), stir for 3-5 minutes at a speed of 1200-1600 rpm, and then transfer to a three-roll mill and grind for 10-20 times to obtain a first mixture of component A; Step A6: placing the first mixture of component A obtained in step (A5) into a planetary vacuum degassing machine, evacuating to below 1 kPa, setting the rotation speed to 800-1000 rpm, and degassing for 3-5 minutes to obtain a thermal conductive component A; (2) Preparation of gel component B: Step B1: adding a portion of cyano-terminated silicone oil to hydrogen-containing silicone oil, heating to 50-70° C., stirring and mixing, controlling the stirring rate at 300-500 rpm for 20-40 minutes, and stirring and cooling to room temperature to obtain a first mixed solution of component B; Step B2: Stir the first mixed solution of component B obtained in step (B2) in an ice water bath at a stirring rate of 300 to 500 rpm, add the treating agent to the first mixed solution of component B, and stir for 10 to 30 minutes to obtain a second mixed solution of component B; Step B3: Keep stirring in an ice-water bath at a stirring rate of 300-500 rpm, add the remaining amount of cyano-terminated silicone oil to the second mixed solution of component B obtained in step (B3), and stir for 1-3 hours to obtain a third mixed solution of component B; Step B4: Keep stirring in an ice-water bath at a stirring rate of 200-400 rpm, slowly dropwise add the complexing agent to the third mixed solution of component B obtained in step (B3), and control the dropping time to be 6-12 minutes. After the dropping is completed, continue stirring for 3-5 minutes, and stir and heat to room temperature under sealing conditions to obtain a fourth mixed solution of component B; Step B5: adding titanium monoxide powder and MgFe2O4 powder to the fourth mixed solution of component B obtained in step (B4) at a high speed of 1200-1600 rpm to obtain a first mixture of component B; Step B6: placing the first mixture of component B obtained in step (B5) into a planetary vacuum degassing machine, evacuating to below 1 kPa, setting the rotation speed to 800-1000 rpm, and degassing for 3-5 minutes to obtain gel component B; (3) Preparation of two-component thermal conductive gel: The obtained thermal conductive component A and gel component B are uniformly mixed in a weight ratio of 1:1, and then cured.

[0015] Specifically, in step A1, 25-35% of linear isopropenyl-terminated silicone oil is added to methacrylate-terminated silicone oil; in step B1, 40-60% of cyano-terminated silicone oil is added to hydrogen-containing silicone oil.

[0016] Beneficial effects: (1) The modifier and treatment agent used in the present invention are respectively suitable for forming a network structure of intermolecular forces of polar molecules in the system of the thermal conductive component A and the gel component B, which is beneficial to the improvement of the thixotropy of the thermal conductive component A and the gel component B and the improvement of the storage stability at room temperature.

[0017] (2) The present invention further improves the thixotropy and room temperature stability of components A and B by compounding linear isopropenyl-terminated silicone oil and cyano-terminated silicone oil and interacting with the modifier and treatment agent of the present invention respectively.

[0018] (3) The cyano-terminated silicone oil in the formula of the present invention is rich in terminal cyano groups, which is beneficial to improving the high-temperature stability of components A and B after the reaction, so that the product of components A and B cured can be used for a long time at a temperature of 200°C.

[0019] (4) The two-component thermally conductive gel of the present invention has the properties of high thermal conductivity, low viscosity, and high thixotropy. It can resist sedimentation and phase separation when stored at room temperature. It is resistant to high temperatures and can be used at 200°C. DETAILED DESCRIPTION

[0020] The present invention can be better understood with reference to the following examples. Example 1

[0021] The two-component thermally conductive gel material of this embodiment includes a thermally conductive component A and a gel component B, and the mass ratio of the thermally conductive component A to the gel component B is 1:1.

[0022] Among them, component A includes the following raw materials in parts by mass: 3 parts of modified silicone oil 1, 2 parts of modified silicone oil 2, 1 part of modifier, 0.01 parts of cross-linking accelerator, 35 parts of filler 1, and 35 parts of filler 2.

[0023] Component B includes the following raw materials in parts by mass: 5 parts of modified silicone oil III, 5 parts of modified silicone oil IV, 5 parts of treating agent, 0.001 parts of complexing agent, 40 parts of filler III, and 35 parts of filler IV.

[0024] In this embodiment, the modified silicone oil 1 is a methacrylate-terminated silicone oil with a branching factor of 0.2 and a dynamic viscosity of 200 cst, and the modified silicone oil 2 is a linear isopropenyl-terminated silicone oil with a dynamic viscosity of 150 cst.

[0025] In this embodiment, the modified silicone oil three is a cyano-terminated silicone oil with a dynamic viscosity of 200 cst and a branching factor of 0.5, and the modified silicone oil four is a hydrogenated silicone oil with a dynamic viscosity of 150 cst and a branching factor of 0.3.

[0026] In this embodiment, the modifier is a mixture of isooctyl octadecanoate and isononyl gluconate in a mass ratio of 1:1.

[0027] In this embodiment, the cross-linking accelerator is manganese oleate.

[0028] In this embodiment, filler 1 is Li7La3Zr2O with a particle size of 30 to 50 microns. 12 Filler 2 is La2Ce2O7 with a particle size of 5~7 microns, filler 3 is titanium monoxide with a particle size of 20~35 microns, and filler 4 is MgFe2O4 with a particle size of 1~2 microns.

[0029] In this embodiment, the treating agent is phenyltriethoxysilane.

[0030] In this embodiment, the complexing agent is oleylamine.

[0031] The preparation method of the two-component thermally conductive gel material of this embodiment includes the following steps: Component A: Step A1: adding 30% of the required amount of modified silicone oil 2 to all the modified silicone oil 1, heating to 40-60° C., stirring and mixing, controlling the stirring rate at 300 rpm for 10 minutes, and stirring and cooling to room temperature to obtain a mixed solution 1 (A); Step A2: Stir the mixed solution 1 (A) obtained in step (A2) in an ice-water bath at a stirring rate of 300 rpm, slowly dropwise add the modifier, and the dropping time is controlled within 1 hour. After the dropping is completed, stir for another 20 minutes to obtain a mixed solution 2 (A); Step A3: Keep stirring in an ice-water bath at a stirring rate of 300 rpm, add the remaining 50% of the modified silicone oil 2 to the mixed solution 2 (A) obtained in step (A3), and stir for 1 hour to obtain a mixed solution 3 (A); Step A4: Keep stirring in an ice-water bath at a stirring rate of 200 rpm, slowly dropwise add a crosslinking accelerator to the mixed solution 3 (A) obtained in step (A3), and the dropping time is controlled within 6 minutes. After the dropping is completed, continue stirring for 3 minutes, and stir and heat to room temperature under sealing conditions to obtain a mixed solution 4 (A); Step A5: Add filler 1 and filler 2 together into the mixed solution 4 (A) obtained in step (A4), stir at a high speed of 1200-1600 rpm for 3 minutes, then transfer to a three-roll mill and grind for 10 times to obtain a mixture 1 (A); Step A6: Place the mixture (A) obtained in step (A5) into a planetary vacuum degassing machine, evacuate to 1 kPa, set the rotation speed to 800 rpm, and degas for 3 minutes to obtain a mixed material of component A.

[0032] Component B: Step B1: adding 50% of the required amount of modified silicone oil 3 to all the modified silicone oil 4, heating to 50° C., stirring and mixing, controlling the stirring rate at 300 rpm for 20 minutes, stirring and cooling to room temperature to obtain a mixed solution 1 (B); Step B2: Stir the mixed solution 1 (B) obtained in step (B2) in an ice water bath at a stirring rate of 300 rpm, add the treatment agent into the mixed solution 1 (B) at one time, and stir for 10 to 30 minutes to obtain a mixed solution 2 (B); Step B3: Keep stirring in an ice-water bath at a stirring rate of 300 rpm, add the remaining 50% of the modified silicone oil 3 to the mixed solution 2 (A) obtained in step (B3), and stir for 1 hour to obtain a mixed solution 3 (B); Step B4: Keep stirring in an ice-water bath at a stirring rate of 200 rpm, slowly dropwise add a crosslinking accelerator to the mixed solution (B) obtained in step (B3), and the dropping time is controlled within 6 minutes. After the dropping is completed, continue stirring for 3 to 5 minutes, and stir and heat to room temperature under sealing conditions to obtain a mixed solution (B); Step B5: Add filler 3 and filler 4 together into the mixed solution 4 (B) obtained in step (B4) at a high speed of 1200 rpm to obtain a mixture 1 (B); Step B6: Place the mixture (B) obtained in step (B5) into a planetary vacuum degassing machine, evacuate to 1 kPa, set the rotation speed to 800 rpm, and degas for 3 minutes to obtain a mixed material of component B; Component A and component B are uniformly mixed in a weight ratio of 1:1 and cured.

[0033] After testing, the viscosity of component A and component B were 460000cp and 470000cp respectively (7# rotor, 10rpm), thixotropic index (7# rotor, η 10rpm / η 1rpm ) are 14.6 and 14.4 respectively, and the thermal conductivity is 5.9 W / (m・K) and 6.0 W / (m・K) respectively.

[0034] The thermal conductivity of component A after the reaction with component B is 5.9 W / (m・K). After treatment at 200℃ for 1000 hours, the thermal conductivity change rate is 2.5%. After treatment at 200℃ for 5000 hours, the thermal conductivity change rate is 3.7%. Example 2

[0035] The two-component thermally conductive gel material of this embodiment includes a thermally conductive component A and a gel component B, and the mass ratio of the thermally conductive component A to the gel component B is 1.2:1.

[0036] Among them, component A includes the following raw materials in parts by mass: 5 parts of modified silicone oil 1, 5 parts of modified silicone oil 2, 3 parts of modifier, 0.05 parts of cross-linking accelerator, 55 parts of filler 1, and 50 parts of filler 2.

[0037] Component B includes the following raw materials in parts by mass: 8 parts of modified silicone oil III, 8 parts of modified silicone oil IV, 8 parts of treating agent, 0.005 parts of complexing agent, 50 parts of filler III, and 40 parts of filler IV.

[0038] In this embodiment, the modified silicone oil 1 is a methacrylate-terminated silicone oil with a branching factor of 0.3 and a dynamic viscosity of 300 cst, and the modified silicone oil 2 is a linear isopropenyl-terminated silicone oil with a dynamic viscosity of 150 cst.

[0039] In this embodiment, the modified silicone oil three is a cyano-terminated silicone oil with a dynamic viscosity of 300 cst and a branching factor of 0.7, and the modified silicone oil four is a hydrogenated silicone oil with a dynamic viscosity of 250 cst and a branching factor of 0.5.

[0040] In this embodiment, the modifier is a mixture of isooctyl octadecanoate and isononyl gluconate in a mass ratio of 1.2:1.

[0041] In this embodiment, the cross-linking accelerator is a mixture of nickel isostearate and cobalt isodecanoate in a mass ratio of 1.2:1.

[0042] In this embodiment, filler 1 is Li7La3Zr2O with a particle size of 50 to 70 microns. 12 Filler 2 is La2Ce2O7 with a particle size of 7~10 microns, filler 3 is titanium monoxide with a particle size of 35~50 microns, and filler 4 is MgFe2O4 with a particle size of 2~3 microns.

[0043] In this embodiment, the treating agent is a mixture of hydrogenated castor oil and palmitic acid in a mass ratio of 1.2:1.

[0044] In this embodiment, the complexing agent is a mixture of dimethyl maleate and tin benzoate in a mass ratio of 1.2:1.

[0045] The preparation method of the two-component thermally conductive gel material of this embodiment includes the following steps: Component A: Step A1: adding 30% of the required amount of modified silicone oil 2 to all the modified silicone oil 1, heating to 40-60° C., stirring and mixing, controlling the stirring rate at 500 rpm for 30 minutes, stirring and cooling to room temperature to obtain a mixed solution 1 (A); Step A2: Stir the mixed solution 1 (A) obtained in step (A2) in an ice-water bath at a stirring rate of 500 rpm, slowly dropwise add the modifier, and the dropping time is controlled within 3 hours. After the dropping is completed, stir for another 40 minutes to obtain a mixed solution 2 (A); Step A3: Keep stirring in an ice-water bath at a stirring rate of 500 rpm, add the remaining 50% of the modified silicone oil 2 to the mixed solution 2 (A) obtained in step (A3), and stir for 3 hours to obtain a mixed solution 3 (A); Step A4: Keep stirring in an ice-water bath at a stirring rate of 400 rpm, slowly dropwise add a crosslinking accelerator to the mixed solution (A) obtained in step (A3), and the dropping time is controlled within 12 minutes. After the dropping is completed, continue stirring for 5 minutes, and stir and heat to room temperature under sealing conditions to obtain a mixed solution (A); Step A5: Add filler 1 and filler 2 together into the mixed solution 4 (A) obtained in step (A4), stir at a high speed of 1600 rpm for 5 minutes, and then transfer to a three-roll mill and grind for 20 times to obtain a mixture 1 (A); Step A6: Place the mixture (A) obtained in step (A5) into a planetary vacuum degassing machine, evacuate to 1 kPa, set the rotation speed to 1000 rpm, and degas for 5 minutes to obtain a mixed material of component A.

[0046] Component B: Step B1: adding 50% of the required amount of modified silicone oil 3 to all the modified silicone oil 4, heating to 70° C., stirring and mixing, controlling the stirring rate at 500 rpm for 40 minutes, stirring and cooling to room temperature to obtain a mixed solution 1 (B); Step B2: Stir the mixed solution 1 (B) obtained in step (B2) in an ice water bath at a stirring rate of 500 rpm, add the treatment agent into the mixed solution 1 (B) at one time, and stir for 30 minutes to obtain a mixed solution 2 (B); Step B3: Keep stirring in an ice-water bath at a stirring rate of 500 rpm, add the remaining 50% of the modified silicone oil 3 to the mixed solution 2 (A) obtained in step (B3), and stir for 3 hours to obtain a mixed solution 3 (B); Step B4: Keep stirring in an ice-water bath at a stirring rate of 400 rpm, slowly dropwise add a crosslinking accelerator to the mixed solution (B) obtained in step (B3), and the dropping time is controlled within 12 minutes. After the dropping is completed, continue stirring for 5 minutes, and stir and heat to room temperature under sealing conditions to obtain a mixed solution (B); Step B5: Add filler 3 and filler 4 together into the mixed solution 4 (B) obtained in step (B4) at a high speed of 1600 rpm to obtain a mixture 1 (B); Step B6: Place the mixture (B) obtained in step (B5) into a planetary vacuum degassing machine, evacuate to 1 kPa, set the rotation speed to 1000 rpm, and degas for 5 minutes to obtain a mixed material of component B; Component A and component B are uniformly mixed in a weight ratio of 1:1 and cured.

[0047] After testing, the viscosity of component A and component B were 410000cp and 430000cp respectively (7# rotor, 10rpm), thixotropic index (7# rotor, η 10rpm / η 1rpm ) are 17.8 and 17.5 respectively, and the thermal conductivity is 6.3 W / (m・K) and 6.4 W / (m・K) respectively.

[0048] The thermal conductivity of component A after the reaction with component B is 6.1 W / (m・K). After treatment at 200℃ for 1000 hours, the thermal conductivity change rate is 2.1%. After treatment at 200℃ for 5000 hours, the thermal conductivity change rate is 3.3%. Example 3

[0049] The two-component thermally conductive gel material of this embodiment includes a thermally conductive component A and a gel component B, and the mass ratio of the thermally conductive component A to the gel component B is 1:1.

[0050] Among them, component A includes the following raw materials in parts by mass: 4 parts of modified silicone oil I, 3 parts of modified silicone oil II, 2 parts of modifier, 0.03 parts of cross-linking accelerator, 45 parts of filler I, and 42 parts of filler II.

[0051] Component B includes the following raw materials in parts by mass: 6 parts of modified silicone oil III, 7 parts of modified silicone oil IV, 6 parts of treating agent, 0.003 parts of complexing agent, 45 parts of filler III, and 37 parts of filler IV.

[0052] In this embodiment, the modified silicone oil 1 is a methacrylate-terminated silicone oil with a dynamic viscosity of 250 cst and a branching factor of 0.25, and the modified silicone oil 2 is a linear isopropenyl-terminated silicone oil with a dynamic viscosity of 200 cst.

[0053] In this embodiment, the modified silicone oil three is a cyano-terminated silicone oil with a dynamic viscosity of 250 cst and a branching factor of 0.6, and the modified silicone oil four is a hydrogenated silicone oil with a dynamic viscosity of 200 cst and a branching factor of 0.4.

[0054] In this embodiment, the modifier is a mixture of isooctyl octadecanoate and isononyl gluconate in a mass ratio of 1.1:1.

[0055] In this embodiment, the cross-linking accelerator is a mixture of manganese oleate and cobalt isodecanoate in a mass ratio of 1.1:1.

[0056] In this embodiment, filler 1 is Li7La3Zr2O with a particle size of 45 to 55 microns. 12 Filler 2 is La2Ce2O7 with a particle size of 7~9 microns, filler 3 is titanium monoxide with a particle size of 30~40 microns, and filler 4 is MgFe2O4 with a particle size of 1.5~2.5 microns.

[0057] In this embodiment, the treating agent is a mixture of phenyltriethoxysilane and palmitic acid in a mass ratio of 1.1:1.

[0058] In this embodiment, the complexing agent is a mixture of oleylamine and dimethyl maleate in a mass ratio of 1.1:1.

[0059] The preparation method of the two-component thermally conductive gel of this embodiment comprises the following steps: Component A: Step A1: adding 30% of the required amount of modified silicone oil 2 to all the modified silicone oil 1, heating to 40-60° C., stirring and mixing, controlling the stirring rate at 400 rpm for 20 minutes, stirring and cooling to room temperature to obtain a mixed solution 1 (A); Step A2: Stir the mixed solution 1 (A) obtained in step (A2) in an ice-water bath at a stirring rate of 400 rpm, slowly dropwise add the modifier, and the dropping time is controlled within 2 hours. After the dropping is completed, stir for another 30 minutes to obtain a mixed solution 2 (A); Step A3: Keep stirring in an ice-water bath at a stirring rate of 400 rpm, add the remaining 50% of the modified silicone oil 2 to the mixed solution 2 (A) obtained in step (A3), and stir for 2 hours to obtain a mixed solution 3 (A); Step A4: Keep stirring in an ice-water bath at a stirring rate of 300 rpm, slowly dropwise add a crosslinking accelerator to the mixed solution (A) obtained in step (A3), and the dropping time is controlled to be 9 minutes. After the dropping is completed, continue stirring for 4 minutes, and stir and heat to room temperature under sealing conditions to obtain a mixed solution (A); Step A5: Add filler 1 and filler 2 together into the mixed solution 4 (A) obtained in step (A4), stir at a high speed of 1400 rpm for 4 minutes, and then transfer to a three-roll mill and grind for 15 times to obtain a mixture 1 (A); Step A6: Place the mixture (A) obtained in step (A5) into a planetary vacuum degassing machine, evacuate to 1 kPa, set the rotation speed to 900 rpm, and degas for 4 minutes to obtain a mixed material of component A.

[0060] Component B: Step B1: Add 50% of the required amount of modified silicone oil 3 to all the modified silicone oil 4, heat to 50-70°C, stir and mix, control the stirring rate at 4 rpm, stir for 30 minutes, and cool to room temperature to obtain a mixed solution 1 (B); Step B2: Stir the mixed solution 1 (B) obtained in step (B2) in an ice water bath at a stirring rate of 400 rpm, add the treatment agent into the mixed solution 1 (B) at one time, and stir for 20 minutes to obtain a mixed solution 2 (B); Step B3: Keep stirring in an ice-water bath at a stirring rate of 400 rpm, add the remaining 50% of the modified silicone oil 3 to the mixed solution 2 (A) obtained in step (B3), and stir for 2 hours to obtain a mixed solution 3 (B); Step B4: Keep stirring in an ice-water bath at a stirring rate of 300 rpm, slowly dropwise add a crosslinking accelerator to the mixed solution (B) obtained in step (B3), and the dropping time is controlled to be 9 minutes. After the dropping is completed, continue stirring for 4 minutes, and stir and heat to room temperature under sealing conditions to obtain a mixed solution (B); Step B5: Add filler 3 and filler 4 together into the mixed solution 4 (B) obtained in step (B4) at a high speed of 1400 rpm to obtain a mixture 1 (B); Step B6: Place the mixture (B) obtained in step (B5) into a planetary vacuum degassing machine, evacuate to 1 kPa, set the rotation speed to 900 rpm, and degas for 4 minutes to obtain a mixed material of component B; Component A and component B are uniformly mixed in a weight ratio of 1:1 and cured.

[0061] After testing, the viscosity of component A and component B were 420000cp and 420000cp respectively (7# rotor, 10rpm), thixotropic index (7# rotor, η10rpm / η 1rpm ) are 15.8 and 16.1 respectively, and the thermal conductivity coefficients are 6.1 W / (m・K) and 6.1 W / (m・K) respectively.

[0062] The thermal conductivity of component A after the reaction with component B is 6.0 W / (m・K). After treatment at 200℃ for 1000 hours, the thermal conductivity change rate is 2.2%. After treatment at 200℃ for 5000 hours, the thermal conductivity change rate is 3.5%. Comparative Example 1

[0063] The commercially available AOK TF600 two-component gel was selected.

[0064] After testing, the viscosity of component A and component B are 3800000cp and 3900000cp respectively (7# rotor, 10rpm), thixotropic index (7# rotor, η 10rpm / η 1rpm ) are 9.1 and 9.2 respectively, and the thermal conductivity is 5.7 W / (m・K) and 5.8 W / (m・K) respectively. The thermal conductivity of component A after the reaction with component B is 5.7W / (m・K). After treatment at 200℃ for 1000 hours, the thermal conductivity change rate is 30.2%. After treatment at 200℃ for 5000 hours, the thermal conductivity change rate is 58.1%.

[0065] The present invention provides a concept and method for a two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy, characterized in that: It includes a heat conductive component A and a gel component B; Wherein, the thermal conductive component A includes the following components by mass: 3-5 parts of methacrylate-terminated silicone oil; 2-5 parts of linear isopropenyl-terminated silicone oil; 1-3 parts of modifier; Cross-linking accelerator 0.01-0.05 parts; Li7La3Zr2O 12 35-55 parts of micro powder; 35-50 parts of La2Ce2O7 powder; Gel component B includes the following components in parts by mass: 5-8 parts of cyano-terminated silicone oil; 5-8 parts of hydrogen silicone oil; 5-8 parts of treatment agent; Complexing agent 0.001-0.005 parts; 40-50 parts of titanium monoxide powder; 35-40 parts of MgFe2O4 fine powder.

2. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: The thermal conductive component A and the gel component B are mixed in a mass ratio of 1-1.2:

1.

3. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: In the thermal conductive component A, the dynamic viscosity of the methacrylate-terminated silicone oil is 200-300 cst, and the branching factor is 0.2-0.3; the dynamic viscosity of the linear isopropenyl-terminated silicone oil is 150-250 cst.

4. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: In the thermal conductive component A, the modifier is a mixture of isooctyl octadecanoate and isononyl gluconate in a mass ratio of 1 to 1.2:1; the cross-linking accelerator is any one of manganese oleate, nickel isostearate, and cobalt isodecanoate, or a mixture of two of them in a mass ratio of 1 to 1.2:

1.

5. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: In the thermal conductive component A, the Li7La3Zr2O 12 The particle size of the micro powder is 30 to 70 microns; the particle size of the La2Ce2O7 micro powder is 5 to 10 microns.

6. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: In the thermal conductive component B, the dynamic viscosity of the cyano-terminated silicone oil is 200-300 cst, and the branching factor is 0.5-0.7; the dynamic viscosity of the hydrogen-containing silicone oil is 150-250 cst, and the branching factor is 0.3-0.

5.

7. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: In the thermal conductive component B, the treatment agent is any one of phenyltriethoxysilane, hydrogenated castor oil, and palmitic acid, or a mixture of two of them in a mass ratio of 1 to 1.2:1; the complexing agent is any one of oleylamine, dimethyl maleate, and tin benzoate, or a mixture of two of them in a mass ratio of 1 to 1.2:

1.

8. The two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: In the thermal conductive component B, the particle size of the titanium monoxide powder is 20-50 microns; the particle size of the MgFe2O4 powder is 1-3 microns.

9. The method for preparing the two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 1, characterized in that: The steps include: (1) Preparation of thermal conductive component A: Step A1: adding a portion of linear isopropenyl-terminated silicone oil to methacrylate-terminated silicone oil, heating to 40-60° C., stirring and mixing, controlling the stirring rate at 300-500 rpm for 10-30 minutes, stirring and cooling to room temperature to obtain a first mixed solution of component A; Step A2: Stir the first mixed solution of component A obtained in step (A1) in an ice-water bath at a stirring rate of 300-500 rpm, slowly dropwise add the modifier, and the dropping time is controlled within 1-3 hours. After the dropping is completed, stir for another 20-40 minutes to obtain a second mixed solution of component A; Step A3: Keep stirring in an ice-water bath at a stirring rate of 300-500 rpm, add the remaining amount of linear isopropenyl-terminated silicone oil to the second mixed solution of component A obtained in step (A3), and stir for 1-3 hours to obtain a third mixed solution of component A; Step A4: Keep stirring in an ice-water bath at a stirring rate of 200-400 rpm, slowly dropwise add a crosslinking accelerator to the third mixed solution of component A obtained in step (A3), and control the dropping time to be 6-12 minutes. After the dropping is completed, continue stirring for 3-5 minutes, and stir and heat to room temperature under sealing conditions to obtain a fourth mixed solution of component A; Step A5: Li7La3Zr2O 12 Add the powder and La2Ce2O7 powder together into the fourth mixed solution of component A obtained in step (A4), stir for 3-5 minutes at a speed of 1200-1600 rpm, and then transfer to a three-roll mill and grind for 10-20 times to obtain a first mixture of component A; Step A6: placing the first mixture of component A obtained in step (A5) into a planetary vacuum degassing machine, evacuating to below 1 kPa, setting the rotation speed to 800-1000 rpm, and degassing for 3-5 minutes to obtain a thermal conductive component A; (2) Preparation of gel component B: Step B1: adding a portion of cyano-terminated silicone oil to hydrogen-containing silicone oil, heating to 50-70° C., stirring and mixing, controlling the stirring rate at 300-500 rpm for 20-40 minutes, and stirring and cooling to room temperature to obtain a first mixed solution of component B; Step B2: Stir the first mixed solution of component B obtained in step (B2) in an ice water bath at a stirring rate of 300 to 500 rpm, add the treating agent to the first mixed solution of component B, and stir for 10 to 30 minutes to obtain a second mixed solution of component B; Step B3: Keep stirring in an ice-water bath at a stirring rate of 300-500 rpm, add the remaining amount of cyano-terminated silicone oil to the second mixed solution of component B obtained in step (B3), and stir for 1-3 hours to obtain a third mixed solution of component B; Step B4: Keep stirring in an ice-water bath at a stirring rate of 200-400 rpm, slowly dropwise add the complexing agent to the third mixed solution of component B obtained in step (B3), and control the dropping time to be 6-12 minutes. After the dropping is completed, continue stirring for 3-5 minutes, and stir and heat to room temperature under sealing conditions to obtain a fourth mixed solution of component B; Step B5: adding titanium monoxide powder and MgFe2O4 powder to the fourth mixed solution of component B obtained in step (B4) at a high speed of 1200-1600 rpm to obtain a first mixture of component B; Step B6: placing the first mixture of component B obtained in step (B5) into a planetary vacuum degassing machine, evacuating to below 1 kPa, setting the rotation speed to 800-1000 rpm, and degassing for 3-5 minutes to obtain gel component B; (3) Preparation of two-component thermal conductive gel: The obtained thermal conductive component A and gel component B are uniformly mixed in a weight ratio of 1:1, and then cured.

10. The method for preparing a two-component thermally conductive gel with high thermal conductivity, low viscosity and high thixotropy according to claim 9, characterized in that: In step A1, 25-35% of linear isopropenyl-terminated silicone oil is added to methacrylate-terminated silicone oil; in step B1, 40-60% of cyano-terminated silicone oil is added to hydrogen-containing silicone oil.

Citation Information

Patent Citations

  • High-strength organic silicon foamed plastic and preparation method thereof

    CN112574567A

  • High-tear-strength heat-conducting silica gel material and preparation method thereof

    CN113563721A

  • Two-component low-viscosity high-thermal-conductivity pouring sealant as well as preparation method and application thereof

    CN115260985A

  • Heat conductive silicone composition

    US20060100336A1

  • Thermally conductive silicone grease and preparation method therefor, and chip assembly

    WO2022218091A1